A Quasi‐Solid‐State Tristate Reversible Electrochemical Mirror Device with Enhanced Stability. Issue 13 (12th May 2020) - Eh, Alice Lee‐Sie; Chen, Jingwei; Yu, Shu Hearn; Thangavel, Gurunathan; Zhou, Xinran; Cai, Guofa; Li, Shaohui; Chua, Daniel H. C.; Lee, Pooi See
Abstract: Reversible electrochemical mirror (REM) electrochromic devices with electrochemical tunability in multiple optical states are exciting alternatives to conventional electrochromic smart windows. Electrochromic devices are studied extensively, yet widespread adoptions have not been achieved due to problems associated with durability, switching speed, limited options on optical states, and cost. In this study, a REM electrochromic device based on CuSn alloy is developed, which offers highly reversible switching between transparent, greyish‐blue, and mirror states via reversible electrodeposition and dissolution. The alloying element, Sn acts as an electrochemical mediator, which facilitates the electrodeposition and dissolution of Cu. The CuSn‐based REM device shows superior cycling stability for 2400 cycles (transmittance mode) and 1000 cycles (reflectance mode). The electrodeposited CuSn alloy film is resistant to surface oxidation in ambient air, with a 2.9% difference in reflectance at 2000 nm after 3 days. In addition, the alloy film exhibits excellent NIR reflectance property with thermal modulation of 18.5 °C at a high temperature of 180 °C. The REM device with zero power consumption maintains its mirror state for at least 100 min, making it a promising candidate for energy‐efficient applications. Abstract : The quasi‐solid‐state tristate reversible electrochemical mirror (REM) device offers highly reversible switching between transparent, greyish‐blue, and mirror states via reversible electrodeposition and dissolution. The REM shows superior thermal barrier property compared to the bare substrate. The extended memory effect of the REM device is achieved in the presence of quasi‐solid‐state polymer electrolyte.